Assessing the association between lifetime exposure to greenspace and early childhood development and the mediation effects of air pollution and noise in Canada: a population-based birth cohort study. Issue 10 (October 2021) - Jarvis, Ingrid; Davis, Zoë; Sbihi, Hind; Brauer, Michael; Czekajlo, Agatha; Davies, Hugh W; Gergel, Sarah E; Guhn, Martin; Jerrett, Michael; Koehoorn, Mieke; Oberlander, Tim F; Su, Jason; et al.
Summary: Background: Exposure to greenspace is associated with improved childhood development, but the pathways behind this relationship are insufficiently understood. Therefore, we aimed to investigate the association between lifetime residential exposure to greenspace and early childhood development and evaluate the extent to which this association is mediated by reductions in traffic-related air pollution and noise. Methods: This population-based birth cohort study comprised singleton births in Metro Vancouver, BC, Canada, between April 1, 2000, and Dec 31, 2005. Children and mothers had to be registered with the mandatory provincial health insurance programme, Medical Services Plan, and have lived within the study area from the child's birth to the time of outcome assessment. Early childhood development was assessed via teacher ratings on the Early Development Instrument (EDI), and we used the total EDI score as the primary outcome variable. We estimated greenspace using percentage vegetation derived from spectral unmixing of annual Landsat satellite image composites. Lifetime residential exposure to greenspace was estimated as the mean of annual percentage vegetation values within 250 m of participants' residential postal codes. Multilevel modelling, adjusted for eight covariates, was used to investigate associations between greenspace exposure and EDI scores. We estimated the mediation effects of nitrogen dioxide (NO2 ), fine particulate matter (PM2·5 ), and noise levels using causal mediation analyses. Findings: Of the 37 745 children born in Metro Vancouver between April 1, 2000, and Dec 31, 2005, 27 372 were included in our final study sample. In the adjusted model, 1 IQR increase in percentage vegetation was associated with a 0·16 (95% CI 0·04–0·28; p=0·0073) increase in total EDI score, indicating small improvements in early childhood development. We estimated that 97·1% (95% CI 43·0–396·0), 29·5% (12·0–117·0), and 35·2% (17·9–139·0) of the association was mediated through reductions in NO2, PM2·5, and noise, respectively. Interpretation: Increased exposure to residential greenspace might improve childhood development by reducing the adverse developmental effects of traffic-related exposures, especially NO2 air pollution. Our study supports the implementation of healthy urban planning and green infrastructure interventions. Funding: Canadian Institutes of Health Research.